ANALISIS PENENTUAN UMUR SISA (REMAINING LIFE ASSESMENT) DAN LAJU KOROSI PADA TANGKI TIMBUN PERTASOL CA T-130 DI UNIT KILANG PPSDM MIGAS CEPU - Chika Vierenna Brata; Hendri Hestiawan; Jamaludin (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
Storage tanks are important infrastructure in the oil and gas industry as a place to store fluids, including refined products such as Pertasol CA. Over time, tanks can experience material degradation due to corrosion, which can threaten operational safety if not carried out regularly. The purpose of conducting a Remaining Life Assessment (RLA) analysis study on storage tanks at the Cepu PPSDM Migas Refinery Unit is to determine the remaining life of the tank based on the material thickness measured using the Ultrasonic Thickness Gauge (UTG) method and calculate the corrosion rate based on API 653 and API 575 standards. Measurements were carried out on the shell (wall) and roof (roof) of the tank, with the results showing that the plate thickness is still above the minimum limit. The highest corrosion rate was found in course 1 at 0.1111 mm/year, with a remaining tank life of approximately 5.04 years. Meanwhile, course 2, course 3, and roof sections each have a remaining life of 19.09 years, 28.37 years, and 14.41 years, respectively. The analysis results indicate that the tank is still suitable for use, but requires regular inspection and maintenance, particularly on parts with high corrosion rates. This research is expected to serve as a reference for maintenance planning and improving the operational safety of storage tanks in the oil and gas industry.